Nitrogen fertilization effect on olive leaf spot and olive anthracnose incidence in the olive tree - Coelho, Valentim (2020)
Nitrogen has a great influence on the canopy development of growing plants and on the composition of plant tissues. Nitrogen fertilization is often associated with increased susceptibility of plants to pests and diseases, and rational fertilization is usually reclaimed as a cultural measure to mitigate their effects. Two field trials were conducted in rainfed olive groves during the years 2017 and 2018, one of the cultivar Madural and the other of cv. Cobrançosa. Three (0, 40 and 120 kg N ha-1) and four (0, 20, 40 and 120 kg N ha-1) nitrogen rates were tested, respectively in 'Cobrançosa') and 'Madural'. In the leaves, the level of incidence of the olive leaf spot (Spilocaea oleagina (Cast.) Hugh.) was visually assessed and after the leaves had been incubated with NaOH (5%). The presence of diseases in the fruit, such as anthracnose (Gloeosporium olivarum Alm.) were also recorded. Olive leaf spot appeared with relatively high incidence in 'Cobrançosa' in 2017 (8.0 to 54.0%) and 2018 (14.0 to 44.7%) and in Madural in 2018 (24.5 to 36.9%), but not related to nitrogen fertilization. Olive anthracnose was relatively high in 2017 in 'Madural' (8.7 to 15.3%) and 'Cobrançoa' (9.7 to 31.3%) and relatively low in 2018 in 'Madural' (2.0 to 8.0%) and Cobrançosa (0.7 to 4.7%), but also unrelated to nitrogen fertilization. These results suggest a reduced influence of nitrogen fertilization on the incidence of olive leaf spot and olive anthracnose, although the high experimental variability suggests that other causes are still to be sought.